Metastatic bladder cancer cells distinctively sense and respond to physical cues of collagen fibril-mimetic nanotopography. (May 2015) - Iuliano, James N; Kutscha, Paul D; Biderman, NJ; Subbaram, Sita; Groves, Timothy R; Tenenbaum, Scott A; Hempel, Nadine
Tumor metastasis is characterized by enhanced invasiveness and migration of tumor cells through the extracellular matrix (ECM), resulting in extravasation into the blood and lymph and colonization at secondary sites. The ECM provides a physical scaffold consisting of components such as collagen fibrils, which have distinct dimensions at the nanoscale. In addition to the interaction of peptide moieties with tumor cell integrin clusters, the ECM provides a physical guide for tumor cell migration. Using nanolithography we set out to mimic the physical dimensions of collagen fibrils using lined nanotopographical silicon surfaces and to explore whether metastatic tumor cells are uniquely able to respond to these physical dimensions. Etched silicon surfaces containing nanoscale lined patterns with varying trench and ridge sizes (65–500 nm) were evaluated for their ability to distinguish between a non-metastatic (253J) and a highly metastatic (253J-BV) derivative bladder cancer cell line. Enhanced alignment was distinctively observed for the metastatic cell lines on feature sizes that mimic the dimensions of collagen fibrils (65–100 nm lines, 1:1–1:1.5 pitch). Further, these sub-100 nm lines acted as guides for migration of metastatic cancer cells. Interestingly, even at this subcellular scale, metastatic cell migration was abrogated when cells were forced to move perpendicular to these lines. Compared to flat surfaces, 65 nm lines enhanced the formation of actin stress fibers and filopodia of metastatic cells. This was accompanied by increased formation of focal contacts, visualized by immunofluorescent staining of phospho-focal adhesion kinase along the protruding lamellipodia. Simple lined nanotopography appears to be an informative platform for studying the physical cues of the ECM in a pseudo-3D format and likely mimics physical aspects of collagen fibrils. Metastatic cancer cells appear distinctively well adapted to sense these features using filopodia protrusions to enhance their alignment and migration.